Exploring the Implementation of Teacher’s Feedback on Students’ Speaking Skill - Rifai, Ahmad Rifai; Rahman, Taufik (Foreign Language Instruction Probe, 2023)
The background of the paper relates to the role of the teacher in the teaching and learning process as well as students as the subjects of that process. The learning and teaching process is primarily teacher-centered. The students had little opportunity to participate actively in class because the teacher constantly explained. Students felt hesitant to express their ideas as a result. They preferred to communicate in Indonesian rather than English. Additionally, they had a tendency to speak incorrectly, mispronouncing words, creating grammatical errors, and making inappropriate remarks. There are several goals for this research. The first is to identify and describe various forms of feedback from teachers on students' speaking activities. The second goal, however, is to have students speak about the reasons for giving such feedback and to explain those reasons. This study used a descriptive qualitative methodology. The research strategy that should describe and explain the phenomenon is the descriptive method. The researches' primary tools were interviews and documentation. Interviews are conducted with both the students and the English teacher who is actively involved in the educational process. However, the lesson plan for an English teacher and a photograph of a teacher in the classroom are used by the researcher as evidence. The results of this study are outside simply describing the various forms of teacher feedback used when educating students in English in the classroom. The researcher then goes on to discuss the various types of feedback that teachers can provide for their students as well as the challenges they face in doing so. The researcher also discusses the issues that students encounter while learning and teaching in relation to teacher feedback.